Microstructural, Mechanical and Fresh-State Performance of BOF Steel Slag in Alkali-Activated Binders: Experimental Characterization and Parametric Mix Design Method - Lucas B. R. Araújo; Daniel L. L. Targino; Lucas F. A. L. Babadopulos; Heloina N. Costa; Antonio E. B. Cabral; Juceline B. S. Bastos (Buildings)
Alkali-activated binders (AAB) are a suitable and sustainable alternative to ordinary Portland cement (OPC), with reductions in natural resource usage and environmental emissions in regions where the necessary industrial residues are available. Despite its potential, the lack of mix design methods still limits its applications. This paper proposes a systematic parametric validation for AAB mix design applied to pastes and concretes, valorizing steel slag as precursors. The composed binders are based on coal fly ash (FA) and Basic Oxygen Furnace (BOF) steel slag. These precursors were activated with sodium silicate (Na2SiO3) and sodium hydroxide (NaOH) alkaline solutions. A parametric investigation was performed on the mix design parameters, sweeping the (i) alkali content from 6% to 10%, (ii) silica modulus (SiO2/Na2O) from 0.75 to 1.75, and (iii) ash-to-slag ratios in the proportions of 75:25 and 50:50, using parametric intervals retrieved from the literature. These variations were analyzed using response surface methodology (RSM) to develop a mechanical model of the compressive strength of the hardened paste. Flowability, yield stress, and setting time were evaluated. Statistical analyses, ANOVA and the Duncan test, validated the model and identified interactions between variables. The concrete formulation design was based on aggregates packing analysis with different paste contents (from 32% up to 38.4%), aiming at self-compacting concrete (SCC) with slump flow class 1 (SF1). The influence of the curing condition was evaluated, varying with ambient and thermal conditions, at 25 °C and 65 °C, respectively, for the initial 24 h. The results showed that lower silica modulus (0.75) achieved the highest compressive strength at 80.1 MPa (28 d) for pastes compressive strength, densifying the composite matrix. The concrete application of the binder achieved SF1 fluidity, with 575 mm spread, 64.1 MPa of compressive strength, and 26.2 GPa of Young’s modulus in thermal cure conditions. These findings demonstrate the potential for developing sustainable high-performance materials based on parametric design of AAB formulations and mix design.